2003
DOI: 10.1097/01.alc.0000078826.10198.31
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Acute Alcohol Load on Metabolism of Skeletal Muscles—Expired Gas Analysis During Exercise

Abstract: The anaerobic threshold, which is the limit of the aerobic glycolytic system (i.e., the so-called aerobic exercise limit) was not influenced by exercise under an acute alcoholic load. However, after the production of lactate started, the respiratory compensation point, which is the limit of the metabolic compensatory action, appeared earlier. This suggested that the intake of alcohol would influence the energy metabolism of skeletal muscles by a mechanism in which the disturbed metabolism of lactate in skeleta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…This clearly indicates that alcohol attenuates the metabolic and respiratory compensation capability and therefore promotes mortality in this model. In a clinical study, Shiraishi and colleagues () found in healthy, intoxicated volunteers that respiratory compensation was influenced by alcohol, as well. Stratifying survivors from nonsurvivors showed that the severity of combined metabolic and respiratory acidosis was promptly increased during hemorrhagic shock in nonsurvivors compared with survivors.…”
Section: Discussionmentioning
confidence: 99%
“…This clearly indicates that alcohol attenuates the metabolic and respiratory compensation capability and therefore promotes mortality in this model. In a clinical study, Shiraishi and colleagues () found in healthy, intoxicated volunteers that respiratory compensation was influenced by alcohol, as well. Stratifying survivors from nonsurvivors showed that the severity of combined metabolic and respiratory acidosis was promptly increased during hemorrhagic shock in nonsurvivors compared with survivors.…”
Section: Discussionmentioning
confidence: 99%
“…Прямое токсическое воздействие этанола и его метаболитов на нейроны обусловлено индуцированием глутаматной нейротоксичности [7] в результате снижения выработки белка нейрофиламентов или нарушения быстрого аксонального транспорта [8]. Этанол активирует тормозные ГАМК-рецепторы и является антагонистом для рецепторов глутамата (N-метил-D-аспарагиновая кислота -NMDA).…”
Section: п а т о г е н е зunclassified
“…This bias is not completely unfounded since many published case series of ethanol intoxicated patients have described a coexistent metabolic acidosis (8,9). Prospective studies using both healthy human volunteers (10,11) and animals (12,13) have linked ethanol intake to the development of a metabolic acidosis.…”
Section: Introductionmentioning
confidence: 99%